KONTRIBUSI SEKTOR TRANSPORTASI TERHADAP PEREKONOMIAN DAERAH DI PROVINSI SUMATERA BARAT - Eliza Eliza (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2017)
The problem that is often faced in development planning, is the inequality and inequality in development. One of the causes, is the uneven spread of investment, either regionally or sectorally. Efforts that can be taken to reduce inequality and inequality in development, is to know the various roles sectoral in development. One sector that contributes to the nation's economy, is the transportation sector. The transportation sector is included in the category of infrastructure development that serves to support all aspects and activities of development. One method that can be used to see the impact of the transport sector on the regional economy and the expansion of employment opportunities in West Sumatra is by using the I-O (Input-Output) Method. This method is able to see the inter-sectoral linkages in the economy, so it can know the performance of a sector (transportation sector) in the regional economy and the appropriate local economic policy in the future. Using the Input-Output Table of West Sumatra, an analysis has been conducted to examine the impact of the transport sector on the regional economy and the extension of employment opportunities in West Sumatra, including the transport sector in general, having a backward link index and a relatively high relative forward index. This situation will have an impact on the development of other sectors and this sector will be responsive to economic change and policy changes in other sectors. Thus, for that reason, the transportation sector deserves to be a priority and strategic sector in the development process.